Strategy for Development of Fish Auction Place at Cilacap Oceanic Fishing Port, Cilacap Regency, Central Java - Siti Annisa Dwi Setiani Nurfadillah; Agus Suherman; Abdul Kohar Mudzakir (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
One of fisheries development goals is to increase production and quality of catches. As one of the functional facilities, Fish Auction Place (FAP) has a very vital role in perspective of economy aspect. Therefore, FAP must be optimized by optimally utilizing facilities and providing good services. The purpose of this study is to analyze the existing conditions in the FAP and develop a strategy for developing the FAP at the Cilacap Ocean Fisheries Port. This research was conducted in October 2020 to January 2021. The research used descriptive method. The data used in this study are primary and secondary data that was obtained from OFP Cilacap. SWOT analysis utilized to analyze the factors in determining the development strategy. The result showed that the condition of the Cilacap Ocean Fishery Port FAP is good but there are some facilities that are not well maintained such as the WWTP. The development strategy obtained at FAP of OFP Cilacap is to improve the quality of FAP management in terms of service, to develop human resources through improving skills with targeted training and management programs, to maintain export quality fish such as tuna, and to carry out maintenance and care. complete FAP facilities towards excellent service